2016
DOI: 10.1002/jcla.22072
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of hematologic parameters in evaluation of massive pulmonary embolism

Abstract: We determined that the levels of NLR and PLR are superior to other parameters in the determination of clinical severity in APE cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
5
25
0
Order By: Relevance
“…simplified PESI). 23,26 Similarly, in this study, PLR was correlated with the simplified PESI, whilst the other two indices lacked such correlation. However, the PLR levels were not different between patient with and without adverse events and it only had a fair predictive performance in predicting in-hospital mortality.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…simplified PESI). 23,26 Similarly, in this study, PLR was correlated with the simplified PESI, whilst the other two indices lacked such correlation. However, the PLR levels were not different between patient with and without adverse events and it only had a fair predictive performance in predicting in-hospital mortality.…”
Section: Discussionsupporting
confidence: 54%
“…15,21,22 Nevertheless, these studies were not consistent so far and some studies failed to find a correlation between MPV and disease severity. 21,23 In this study, the simplified PESI outperformed the platelet indices in prognosticating patients with acute PTE. Akgülü et al in a study showed that the predictive performance of extensively-studied risk scores such as the simplified PESI can be improved by addition of factors such as MPV.…”
Section: Discussionmentioning
confidence: 70%
“…21 The variations observed may be due to differences between study populations with ours having substantially less patients with massive PE compared to the cohort studied by Ates et al (n ¼ 13 vs n ¼ 218). 21 Furthermore, our exclusion criteria did not encompass conditions such as heart failure, RV and LV dysfunction, intracardiac thrombus, pericardial effusion, nephrotic syndrome, acute renal and liver failure, endocrine disorders, major surgical interventions, major trauma, and intubation. 21 Future studies in acute PE should consider the prognostic utility of serial NLR and PLR measurements since inflammation is a dynamic process.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, Ates et al found that PLR was significantly elevated in patients with massive PE compared to patients with submassive or low-risk PE. 21 It is worth noting that other studies have observed an elevation of PLR in patients with RV dysfunction and a positive correlation between PLR and RV/LV ratio. 19,22 In fact, PLR has also been positively correlated with CT pulmonary artery obstruction index, suggesting that higher PLR is associated with increased thrombus burden.…”
Section: Discussionmentioning
confidence: 77%
“…While this high value increased along the severity of the disease, there was no difference observed between patients with thrombosis development and those without 27 . Similarly, studies on pulmonary embolism patients showed a linear relationship between PLR values and the severity of the disease, and found it closely related to mortality [28][29][30] . In addition to these, in the study by Yang et al on cancer patients, PLR values over 260 were found to be an independent risk factor for development of venous thrombosis 22 .…”
Section: Discussionmentioning
confidence: 89%